The Application of a Depreciation Charge in Railway Accounting - Delano, Frederic A. (Journal of Political Economy, 1908)
The Interstate Commerce Commission have already intro? duced into Railway Accounts, beginning with July 1, 1907, the principle of making a fixed monthly charge for depreciation of equipment (locomotives, passenger and freight cars, work-train equipment and tools) and have furthermore suggested that the principle should be applied to track, bridges, and buildings, and minor structures. Under these circumstances, it seems desirable to set forth somewhat fully the methods of dealing with this general subject which have been developed in this country and in Great Britain during the last seventy-five years; and if possible, arrive at a fair conclusion as to the best course to adopt. Furthermore, while in some parts of the country it may be to the interest of railroad corporations to swell their operating expenses as much as possible; or in other parts of the country it may be to their interest to make the operating expenses appear as low as possible, this question of depreciation should not be considered from the standpoint of selfish or local interests, but rather from the standpoint of the broad principles involved, which apply very generally to many commercial undertakings. Nothing in this paper is intended as in any sense a reflection or attack upon the rulings of the Interstate Commerce Com? mission; but is an endeavor to co-ordinate the facts in relation to the subject and point out wherein these rules for depreciation are both unjust and unwise in their method of application.